Some Remarks On The Results Of Archaeological Research In The Funerary Structures Of The Settled And CattleBreeding Population Of The Khorezm Oasis (Texas Journal of Philology, Culture and History, 2025)
This article examines the specific features of the burial structures of the sedentary population and pastoral tribes of the South Aral Sea region based on the analysis of archaeological artifacts found in them.